Antibiotic prescribing patterns in patients hospitalized with COVID-19: lessons from the first wave. Issue 2 (30th June 2021) - O'Kelly, Brendan; Cronin, Colm; Connellan, David; Griffin, Sean; Connolly, Stephen Peter; McGrath, Jonathan; Cotter, Aoife G; McGinty, Tara; Muldoon, Eavan G; Sheehan, Gerard; Cullen, Walter; Doran, Peter; et al.
Abstract: Background: A high proportion of hospitalized patients with COVID-19 receive antibiotics despite evidence to show low levels of true bacterial coinfection. Methods: A retrospective cohort study examining antibiotic prescribing patterns of 300 patients sequentially diagnosed with COVID-19. Patients were grouped into 3 sub-cohorts: Group 1 received no antibiotics, Group 2 received antibiotics for microbiologically confirmed infections and Group 3 was empirically treated with antibiotics for pneumonia. The primary aim was to identify factors that influenced prescription and continuation of antibiotics in Group 3. Secondary aims were to examine differences in outcomes between groups. Results: In total, 292 patients were included (63 Group 1, 35 Group 2, 194 Group 3), median age was 60 years (IQR 44–76) and the majority were ethnically Irish (62%). The median duration of antibiotics was 7 days (IQR 5–10). In Group 3, factors associated with prescription IV antibiotics on admission were raised C-reactive protein (CRP) ( P = 0.024), increased age ( P = 0.023), higher quick SOFA ( P = 0.016) score and fever >37.5 °C ( P = 0.011). Factors associated with duration of antibiotic course were duration of hypoxia ( P < 0.001) and maximum respiratory support requirement ( P = 0.013). Twenty-one patients in Group 3 had one or more antibiotic escalation events, most ( n = 139) had no escalation or de-escalation of therapy. Conclusions: Duration of hypoxia and need for respiratory support may have acted as surrogate measures of improvement where usual response measures (CRP, neutrophilia, culture clearance) were absent. Continuous review of antibiotic prescriptions should be at the forefront of clinical management of hospitalized patients with COVID-19.